2004
DOI: 10.1002/art.20040
|View full text |Cite
|
Sign up to set email alerts
|

Association of a programmed death 1 gene polymorphism with the development of rheumatoid arthritis, but not systemic lupus erythematosus

Abstract: Objective. The expression of autoimmunity in mice deficient in programmed death 1 (PD-1) suggests that PD-1 is a candidate gene involved in the development of human autoimmune diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). We therefore tested the potential association between PD-1 and the development of SLE and RA by conducting case-control genetic-association studies.Methods. Ninety-eight SLE patients, 84 RA patients, and sex-matched control subjects for each disease group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
1
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(101 citation statements)
references
References 29 publications
3
85
1
12
Order By: Relevance
“…40 We have shown here that two of the PDCD1 SNPs influencing IgE responses also confer susceptibility to RA. Prokunina et al 41 and Lin et al 42 have also very recently reported associations of distinct single PDCD1 SNPs with RA in studies of relatively small cohorts (PD-1 þ 7078 and PD-1 þ 7717, respectively). The significance of these observations is questionable, however, given that, for the Taiwanese cases studied by Lin et al, the locus did not exhibit Hardy-Weinberg equilibrium, and that the association reported by Prokunina et al was relatively weak (P ¼ 0.053).…”
Section: Discussionmentioning
confidence: 95%
“…40 We have shown here that two of the PDCD1 SNPs influencing IgE responses also confer susceptibility to RA. Prokunina et al 41 and Lin et al 42 have also very recently reported associations of distinct single PDCD1 SNPs with RA in studies of relatively small cohorts (PD-1 þ 7078 and PD-1 þ 7717, respectively). The significance of these observations is questionable, however, given that, for the Taiwanese cases studied by Lin et al, the locus did not exhibit Hardy-Weinberg equilibrium, and that the association reported by Prokunina et al was relatively weak (P ¼ 0.053).…”
Section: Discussionmentioning
confidence: 95%
“…The observation that an inherited variation in CD24 predisposes to both MS and SLE is intriguing, and supports current hypotheses that common cellular and molecular pathogenetic mechanisms might be involved in multiple inflammatory diseases. The general observation that other inflammatory and autoimmune diseases are associated with the same genes (e.g., CTLA4 [27], PTPN22 [28][29][30], and PDCD1 [31][32][33][34]) suggests it may be useful to evaluate the role of CD24 in other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover PD 1.3 SNP has been reported in different autoimmune settings, including rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 30 SNPs have been identified in human PD-1 gene [10,11]. Prokunina et al reported that the allele A of a SNP named PD1.3 (PD1.3A) in intron 4 is associated with the development of SLE in Europeans (relative risk=2.6) and Mexicans (relative risk=3.5) [12] To date, Single Nucleotide Polymorphism association with PD 1.3 has been reported in several auto-antibody associated autoimmune diseases; including psoriasis [13], rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Introductionmentioning
confidence: 99%